My life in leadership the journey and lessons learned along the way - Hesselbein, Frances (Jossey-Bass, 2011)
"The extraordinary life of an extraordinary leader: Frances Hesselbein Leadership is a Journey is written in a personal, intimate tone that delivers key leadership lessons applicable to leaders in every walk of life. Tracing her development as a leader, Hesselbein tells her inspirational story around a dozen guiding principles. The stories will show what shaped her personally and professionally: stories from her childhood, as CEO transforming the Girl Scouts and then transforming that organization, being handpicked by Peter Drucker to found and lead the Drucker Foundation, transitioning the foundation to the Leader to Leader Institute and travelling the world to deliver her message of leadership to thousands. Discusses Hesselben's experiences with Peter Drucker, John Gardner, Max DePree, President Clinton, General Shinseki, Jim Collins, Marshall Goldsmith, and others Reveals the author's personal and professional stumbling blocks and triumphs as one of our nation's foremost nonprofit leaders Includes leadership lesson for anyone who is in a leadership position As inspirational as it is information, this book is filled with larger than life stories and key leadership lessons that can be applied in daily life"--
Includes index. - Print version record
Keywords: Hesselbein, Frances; Girl Scouts of the United States of America -- Management; Peter F. Drucker Foundation for Nonprofit Management; Women chief executive officers -- Biography -- United States; Leadership; Girl Scouts of the United States of America; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; BIOGRAPHY & AUTOBIOGRAPHY; General; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; Management; Women chief executive officers; United States; autobiographies (literary works); Autobiographies; Biographies; Autobiography; Biography